Transcultural adaptation into Portuguese of an instrument for pain evaluation based on the biopsychosocial model - Monique Rocha Peixoto dos Santos; Leandro Calazans Nogueira; Ney Armando Meziat-Filho; Rob Oostendorp; Felipe José Jandre dos Reis
Abstract Introduction: Pain is an individual experience influenced by multiple interacting factors. The "biopsychosocial" care model has gained popularity in response to growing research evidence indicating the influence of biological, psychological, and social factors on the pain experience. The implementation of this model is a challenge in the practice of the health professional. Objective: To perform the transcultural adaptation of the SCEBS method into Brazilian Portuguese. Methods: The instrument was translated and applied to 50 healthy subjects and 50 participants with non-specific chronic pain in the spine. The process of cross-cultural adaptation included the following steps: transcultural adaptation, content analysis of the scale, pre-test, revision, back-translation review, cross-cultural adaptation, revised text correction and final report. Results: The translated and adapted 51-item Portuguese version of the SCEBS method produced an instrument called SCEBS-BR. In the assessment by the target population, 50 adult users of the Brazilian Unified Health System answered the questionnaire and showed good understanding of the instrument on the verbal rating scale. Conclusion: The SCEBS-BR was proved to be easily understandable, showing good semantic validation regardless of schooling level or age, and can be considered adequate for clinical use.